KEBIJAKAN PAJAK DALAM MEMBANTU PEREKONOMIAN PADA MASA RESESI EKONOMI BERDASARKAN PERSPEKTIF ISLAM - novita sari; Muhammad Iqbal Fasa; Suharto Suharto (Fakultas Ekonomi Universitas Bangka Belitung, 2021)
The economic recession is marked by a weak global economy, which can affect the economy simultaneously resulting in all company profits, employment, and investment will decrease as well as state income in the field of taxation, the government continues to issue policies due to this impact. Tax policy made to provide tax relief. The study used qualitative methods, with a descriptive approach obtained with secondary data. Regarding tax relief in an Islamic perspective, it is known as Rukhsah which aims to be able to help the community in reorganizing its economy. The benefit is that the community's economy will improve and can make state income from the tax sector stable. Keywords: Economic recession, taxes, tax deductions, state income.